EStudo fundamental da interação de nanopartículas metálicas com íons terras raras em vidros e vitrocerâmicas para aplicações na região do infravermelho - Silva, Mariana Carolina de Castro [UNESP] (2015)
This work aimed to study the energy transfer processes in both glasses and glass-ceramics containing silver nanoparticles and rare earth ions. Two vitreous systems were chosen for this study 50GeO2-50PbO doped with 1, 3 and 5 mol % AgCl and Eu2O3 at concentrations, ranging from 0.2 to 1 mol %, and the system 50GeO2-20Bi2O3-20PbO-10BaO doped with 3 mol % AgCl and 1 mol % Er2O3. The glassy samples were prepared by melt-quenching methodology. Nanoparticles were prepared by controlled thermal treatment of the glass at temperatures determined by thermal analysis. Thermal, structural and optical properties of glasses were systematically studied by thermal analysis (DSC), Raman, UV-Vis, M-lines and luminescence spectroscopy. The morphology of the nanoparticles was evaluated by transmission electron microscopy. The luminescence results obtained for the binary system showed that the addition of silver increases the emission of europium ions in comparison to the glass without silver. Heat treatment process was performed below the glass transition temperature, however, it induced a heterogeneous crystallization process during the formation of the glass-ceramics. For such reason, it has become difficult to compare the results of luminescence. The luminescence results of the quaternary system also showed an increase of emission after addition of silver, but in this case the ion studied was erbium and the emission was in the near infrared region. The controlled heat treatment led to a homogeneous crystallization process through the glass. The results suggest that two luminescence energy transfer mechanisms may exist. The first is decisive in glasses with low heat treatment time what induces low concentration of nanoparticles. In such case, an increase of emission intensity in the infrared was observed suggesting energy transfer from the nanoparticle to the rare earth ion. The second is observed in samples...